2012
DOI: 10.1093/geront/gns103
|View full text |Cite
|
Sign up to set email alerts
|

Hospital Readmission Among Older Adults Who Return Home With Unmet Need for ADL Disability

Abstract: Many older patients are discharged from the hospital with ADL disability. Those who report unmet need for new ADL disabilities after they return home from the hospital are particularly vulnerable to readmission. Patients' functional needs after discharge should be carefully evaluated and addressed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
117
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 140 publications
(120 citation statements)
references
References 27 publications
3
117
0
Order By: Relevance
“…We had hypothesized that disability limitations measured as ADL limitations would be significant predictors of readmission for all the cohorts, supported by literature data. [10][11][12][13][14][15][16][17][18][19][39][40][41][42] Although ADL limitations were significant predictors of readmission for pneumonia using the HRS-CMS and ACS-HCUP data sets, this was not demonstrated for the heart failure or acute myocardial infarction cohorts. Cognitive impairment did not predict readmission in any cohort for either data set, perhaps because the diagnosis of dementia is part of the standard CMS risk adjustment already applied.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We had hypothesized that disability limitations measured as ADL limitations would be significant predictors of readmission for all the cohorts, supported by literature data. [10][11][12][13][14][15][16][17][18][19][39][40][41][42] Although ADL limitations were significant predictors of readmission for pneumonia using the HRS-CMS and ACS-HCUP data sets, this was not demonstrated for the heart failure or acute myocardial infarction cohorts. Cognitive impairment did not predict readmission in any cohort for either data set, perhaps because the diagnosis of dementia is part of the standard CMS risk adjustment already applied.…”
Section: Discussionmentioning
confidence: 99%
“…7 However, an increasing body of literature reveals that patient disability and social determinants of health impact readmission risk and vary across hospital populations, contributing to higher readmission penalties for safety-net hospitals-and generating increasing interest in studying risk adjustment for sociodemographic factors. 1,[8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] To provide a better understanding of the extent to which the addition of patient disability and social determinants of health would impact the current risk adjustment models used by CMS, the objective of our study was to assess how measures of disability and social determinants of health were associated Electronic supplementary material The online version of this article (doi:10.1007/s11606-016-3869-x) contains supplementary material, which is available to authorized users.…”
Section: T He Centers For Medicare and Medicaid Services (Cms)mentioning
confidence: 99%
“…Our findings also build on smaller or single-site studies showing a consistent relationship between functional impairment and readmission. 13, 16, 17, 18 …”
Section: Commentmentioning
confidence: 99%
“…Existing studies have suggested a relationship but are limited by single-site data, short duration of follow up, or small sample size which cannot be reliably extrapolated broadly to the entire Medicare population. 16,17, 18 Functional impairment has also been hypothesized to play a key role in “post-hospitalization syndrome” that may predispose older, vulnerable adults to readmission. 19 Unfortunately, previous high-quality readmission studies which rely on Medicare data have been unable to assess the effects of functional impairment because functional status of hospitalized Medicare beneficiaries is not reported to CMS.…”
Section: Introductionmentioning
confidence: 99%
“…These events can lead to the decline or loss of functional capacity. [3][4][5][6] Authors 7-8 alert to the possibility of this functional decline of the elderly prior to the admission, which can happen two weeks before the need for hospitalization. There is also the possibility of the long-living elderly being caught on a vicious cycle of loss of functional capacity, hospitalization and loss of functional capacity.…”
Section: Introductionmentioning
confidence: 99%